Beijing Garbage A City Besieged by Waste - Landsberger, Stefan; Project Muse. (Amsterdam University Press, 2019)
Why do central and local government initiatives aiming to curb the proliferation of garbage in Beijing and its disposal continue to be unsuccessful? Is the Uberization of waste picking through online-to-offline (O2O) garbage retrieval companies able to decrease waste and improve the lives of waste pickers? Most citizens of Beijing are well aware of the fact that their city is besieged by waste. Yet instead of taking individual action, they sit and wait for the governments at various levels to tell them what to do. And even if/when they adopt a proactive position, this does not last. Official education drives targeting the consumers are organized regularly and with modest success, but real solutions are not forthcoming. Various environmental non-governmental organizations are at work to raise the level of consciousness of the population, to change individual attitudes towards wasteful behavior, but seemingly with little overall effects.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Abfall; Refuse and refuse disposal -- Management; Refuse and refuse disposal -- Government policy; Refuse and refuse disposal -- China -- Beijing -- Management; Refuse and refuse disposal -- Government policy -- China -- Beijing; Peking; China; China -- Beijing; Electronic books